Hyperemesis gravidarum in premarital pregnancy: scoping review - Nurhidaya Fitria; Cesa Septiana Pratiwi; Menik sri daryanti (Universitas 'Aisyiyah Yogyakarta, 2022)
Hyperemesis gravidarum is the main cause of death, currently the hyperemesis gravidarum is no longer the main cause of maternal mortality, however the hyperemesis gravidarum is still the main cause of maternal mordibility. The cause of hyperemesis gravidarum is not yet known with certainty, with an incidence of 2/1000 pregnancies. Several influences have factors, including predisposing factors (primigravida, hydatidiform mole, and multiple pregnancy). Organic factors (allergies, entry of chorial villi in the circulation, metabolic changes due to pregnancy, and the maternal resistance is decreased). Psychological factors (age, household, job loss, fear). The method used through five stages, namely identifying scoping review questions with the PEOT framework (Population, Exposure, Outcome, and Thema), identifying articles using relevant databases (PubMed, Ebsco, Wiley, Science Direct) and gray literature (Google Scholar). by using keywords, article selection, data charting, compiling, summarizing and reporting results. Five articles had the highest and lowest scores. Four themes emerged as a result of the scoping review, it consisted of the prevalence, incidence, degree and management of hyperemesis gravidarum in premarital pregnancy.